Profesionalisme Dan Independensi Auditor Terhadap Kualitas Audit Laporan Keuangan Dengan Etika Auditor Sebagai Variabel Moderasi - Bagus Satria Asfan; Ceacilia Srimindarti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Audit quality is every possibility that the auditor will find and report violations of the accounting system based on the auditing standards that have been set. The aim of this research is to test the influence of auditors’ professionalism and independence on audit quality and how the auditor ethics can moderate those independent variables to dependent variable. The sample used in this study was 62 auditors at the Public Accounting Firm in Central Java (senior auditors, junior auditors, manager and partners) in 2023. The study used questionnaires as the data collecting method that distributed directly to the auditor who works in Central Java. Then it analysed by using Partial Least Square (PLS) analysis. The results of the reseach showed that (1) the professionalism affect the audit quality significantly, (2) the independence affect the audit quality significantly, (3) auditor ethics is unable to moderate (strengthen) the influence on audit quality professionalism, (4) auditor ethics is unable to moderate (strengthen) the influence on audit quality independence. Keywords: : Professionalism, Independence, Audit Quality, Auditor Ethics